Chemical phases analysis of Barium in Ores by X-ray Fluorescence Spectroscopy - Xiao Wang; Jiufen Liu; Boxin Feng; Xiaofeng Zhao; Ronghua Li; Liming Gan; Na Guo (PLoS ONE, 2025)
Accurately determining the phase states of barium carbonate, barium silicate, and barium sulfate in ores. It’s crucial for advancing research on barium ore mineralization and improving beneficiation and smelting processes. This study aimed to investigate the integration of phase analysis and X-ray fluorescence spectrometry(XRF) to assess the phases of barium in ores, only requiring simple sample pretreatment before measurement. The acetic acid separation drip method was used for the determination of barium carbonate, while the hydrochloric acid separation drip method was used for barium silicate. Additionally, the fusion sample preparation method was applied for the analysis of barium sulfate. The results were consistent with those obtained using chemical methods, and the precision of the relative standard deviation(RSD) was less than or equal to 2.74%, satisfying the analytical requirements. This study combines chemical separation with XRF for continuous and precise phase determination. This approach enhances applicability of XRF in chemical phase analysis and provides a simpler, more environmentally friendly alternative to traditional techniques. It can be applied to barium phase analysis in general barium ores.